2016
DOI: 10.22146/jieb.10312
|View full text |Cite
|
Sign up to set email alerts
|

How Does Congestion Matter for Jakarta’s Citizens?

Abstract: Jakarta, as the biggest city in Indonesia, faces many problems, one of which is congestion, that produces a high cost economy. It is predicted that if the government does not take immediate action to solve this problem, there will be a potential loss of IDR65 trillion by 2020 (Bappenas, 2007). This consists of IDR28.1 trillion in operational costs and IDR36.9 trillion in opportunity costs from time lost. This study is aimed at estimating how much Jakarta citizens' are willing to pay to overcome the congestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…In the case of Jakarta as the center of government, business & trade, services and as a center of mobility, the result is that many private vehicles are the main cause of traffic jams [47]. There are 141 congestion points dispersed throughout various regions of DKI Jakarta.…”
Section: The Urgency Of Relocating the Capital Of Jakartamentioning
confidence: 99%
“…In the case of Jakarta as the center of government, business & trade, services and as a center of mobility, the result is that many private vehicles are the main cause of traffic jams [47]. There are 141 congestion points dispersed throughout various regions of DKI Jakarta.…”
Section: The Urgency Of Relocating the Capital Of Jakartamentioning
confidence: 99%
“…From the economic perspective, this issue has been investigated by Harmadi et al (2015) who observed the willingness of the people in Jakarta to compensate in terms of money for averting traffic congestion. Their study noted that on average, 17 per cent of the private car users were willing to pay additional costs to avoid traffic congestion.…”
Section: Age Segmentation For Predicting Behavioural Intention Of Usimentioning
confidence: 99%
“…From the Asian Journal of Business and Accounting 11(1), 2018 social science perspective, Khafian (2013) suggested that sustainable transportation policy can be a part of the solution for overcoming the traffic congestion problem in Jakarta. Existing studies (Harmadi et al, 2015;Khafian, 2013;Gaduh et al, 2017) have provided some useful insights into the congestion problem in Jakarta but these are limited in scope. To the best of the authors' knowledge, little work has been done to explore this issue from the consumer's behavioural perspective.…”
Section: Age Segmentation For Predicting Behavioural Intention Of Usimentioning
confidence: 99%
See 1 more Smart Citation
“…Dalam konteks Indonesia, kelemahan dalam regulasi tersebut diyakini memiliki keterkaitan dengan kompleksitas tata kelola perkotaan terhadap upayaupaya untuk meningkatkan keterhubungan serta mobilitas yang sifatnya berkelanjutan. Hingga saat ini, isu kemacetan di Jakarta telah mencapai tahap yang mengkhawatirkan dimana pada tahun 2020 potential loss diperkirakan mencapai 65 Triliun Rupiah (Harmadi et al, 2015). Meskipun belum terdapat penelitian mengenai excess commuting di JMA, namun situasi ini jelas mengindikasikan tingginya ketidakseimbangan pada lokasi rumah dan tempat bekerja.…”
Section: Permasalahan Komuter Perkotaanunclassified